Comparison of the effects of fentanyls and other μ opioid receptor agonists on the electrical activity of respiratory muscles in the rat - Cavallo, Damiana; Kelly, Eamonn; Henderson, Graeme; Abdala Sheikh, Ana Paula (Frontiers in Pharmacology, 2023)
Deaths due to overdose of fentanyls result primarily from depression of respiration. These potent opioids can also produce muscle rigidity in the diaphragm and the chest muscles, a phenomenon known as Wooden Chest Syndrome, which further limits ventilation. We have compared the depression of ventilation by fentanyl and morphine by directly measuring their ability to induce muscle rigidity using EMG recording from diaphragm and external and internal intercostal muscles, in the rat working heart-brainstem preparation. At equipotent bradypnea-inducing concentrations fentanyl produced a greater increase in expiratory EMG amplitude than morphine in all three muscles examined. In order to understand whether this effect of fentanyl was a unique property of the phenylpiperidine chemical structure, or due to fentanyl’s high agonist intrinsic efficacy or its lipophilicity, we compared a variety of agonists with different properties at concentrations that were equipotent at producing bradypnea. We compared carfentanil and alfentanil (phenylpiperidines with relatively high efficacy and high to medium lipophilicity, respectively), norbuprenorphine (orvinolmorphinan with high efficacy and lipophilicity) and levorphanol (morphinan with relatively low efficacy and high lipophilicity). We observed that, agonists with higher intrinsic efficacy were more likely to increase expiratory EMG amplitude (i.e., produce chest rigidity) than agonists with lower efficacy. Whereas lipophilicity and chemical structure did not appear to correlate with the ability to induce chest rigidity.